Prognostic value of the Geriatric Nutritional Risk Index in mortality prediction among critically ill acute myocardial infarction patients - Shanshan Tang; Chengcheng Wu; Yanbin Su; Yongle Li (BMC Cardiovascular Disorders)
Abstract Background Nutritional status is a key factor influencing outcomes in critically ill patients with acute myocardial infarction (AMI). This study investigated the association between the Geriatric Nutritional Risk Index (GNRI) and mortality among ICU-admitted AMI patients, as well as GNRI’s potential to improve the predictive accuracy of current scoring systems. Methods In this retrospective cohort study, data from 5,506 ICU-admitted AMI patients were sourced from three open-access critical care databases. Based on GNRI scores, patients were grouped into two categories: GNRI ≤ 98 and GNRI > 98. Statistical tools such as logistic regression and Cox proportional hazards models assessed in-hospital and 30-day mortality. Kaplan-Meier survival curves and restricted cubic splines analyzed survival trends and dose-response relationships. Sensitivity analyses, including propensity score matching (PSM), inverse probability weighting (IPW), and dropping missing data analysis validated the robustness of findings. The receiver operating characteristic (ROC) curve compared GNRI’s predictive ability with SOFA and APSIII scores. A sensitivity analysis was performed using a four-tier GNRI classification: no risk (> 98), low risk (92–98), moderate risk (82–<92), and major risk (< 82) to further explore its gradient relationship with mortality. Results Patients with GNRI ≤ 98 showed higher mortality rates for in-hospital (21.8% vs. 10.4%) and 30-day (22.5% vs. 10.7%) outcomes. GNRI displayed an inverse correlation with in-hospital mortality (OR 0.51, 95% CI 0.43–0.60) and 30-day mortality (HR 0.57, 95% CI 0.50–0.66), even after adjusting for confounders. Subgroup analysis emphasized GNRI’s reliability as a predictive marker, particularly in patients with eGFR ≥ 90. ROC analysis confirmed GNRI’s predictive performance (AUC = 0.64) and its enhancement of SOFA (AUC = 0.72) and APSIII (AUC = 0.66) scores (all p < 0.001). Sensitivity analyses reinforced GNRI’s link to mortality. Conclusion GNRI serves as a robust predictor of in-hospital and 30-day mortality among critically ill AMI patients. Its integration with existing scoring systems improves risk stratification in this high-risk population.